Common Fixed Point of Two R-Weakly Commuting Mappings in b-Metric Spaces. (18th May 2015) - Kumam, Poom; Sintunavarat, Wutiphol; Sedghi, Shaban; Shobkolaei, Nabi
Abstract : We prove some common fixed point results for two mappings satisfying generalized contractive condition inb -metric space. Note thatb -metric of main results in this work are not necessarily continuous. So our results extend and improve several previous works. We also present one example that shows the applicability and usefulness of our results.